Validation of the Brazilian-Portuguese Version of a Short Questionnaire to Assess Knowledge in Cardiovascular Disease Patients (CADE-Q SV) - Ghisi,Gabriela Lima de Melo (2018)
Abstract Background: Patient education is an essential part of cardiovascular patients' care targeting self-management behavior to reduce risk factors and subsequent events. Herein, a short and reliable tool to assess patients' knowledge in Brazil is warranted. Objectives: To translate, culturally-adapt and psychometrically validate the Portuguese version of the Coronary Artery Disease Education Questionnaire Short Version (CADE-Q SV). Methods: The Portuguese CADE-Q SV - translated and culturally-adapted - was reviewed by five bilingual experts in cardiovascular disease. This version was then pre-tested in 21 patients, and clarity of items was checked using a Likert-type scale ranging from 1 = not clear to 10 = very clear. It was then psychometrically tested in 200 cardiovascular patients (41%women; mean age = 58.4 ± 11.6 years old). The internal consistency was assessed using Kuder-Richardson-20 (KR-20) and Cronbach's alpha, test-retest reliability through intraclass correlation coefficient (ICC), factor structure using confirmatory factor analysis, and construct validity regarding educational level, family income, and time of diagnosis. Results: All questions were considered clear by patients (clarity range:7.8-9.6). KR-20 was 0.70. All ICC values were > 0.70. Factor analysis revealed 6 factors, all internally consistent. Construct validity was supported by significant differences in total scores by educational level and family income (p < 0.001). The overall mean was 13.08 ± 2.61. The area with the highest knowledge was risk factors and the lowest was psychosocial risk. Conclusions: The Portuguese CADE-SV was demonstrated to have good validity and reliability. This tool can be applicable in clinical and research settings, assessing cardiovascular patients' knowledge as part of an education programming.